New and little-known Mantophasmatidae (Insecta: Mantophasmatodea) from European amber - Perkovsky, Evgeny E.; Vasilenko, Dmitry V.; Storozhenko, Sergey Yu. (Zootaxa, 2024)
Two new species of gladiators are described from European amber, namely Raptophasma neli sp. nov. and Adicophasma hafniensis sp. nov. from Baltic and Danish amber, respectively. Two names are resurrected from synonyms: Adicophasma Engel & Grimaldi, 2004, nom. resurr. and A. spinosum Engel & Grimaldi, 2004, nom. resurr. Original combination is restored for A. grylloblattoides Arillo & Engel, 2006, comb. resurr. Adicophasma groehni (Zompro, 2008), comb. nov. is tranferred from Raptophasma to Adicophasma. As a result, the ancient subfamily Raptophasmatinae nowadays consists of one Jurassic monotypic genus and two Eocene genera with six species from European amber.